2005
DOI: 10.1074/jbc.m410650200
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Erythrocyte Membrane Mechanical Function by Protein 4.1 Phosphorylation

Abstract: Erythrocyte membrane mechanical function is regulated by the spectrin-based membrane skeleton composed of ␣-and ␤-spectrin, actin, protein 4.1R (4.1R), and adducin. Post-translational modifications of these proteins have been suggested to modulate membrane mechanical function. Indeed, ␤-spectrin phosphorylation by casein kinase I has been shown to decrease membrane mechanical stability. However, the effects of the phosphorylation of skeletal proteins by protein kinase C (PKC), a serine/threonine kinase, have n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
192
0
5

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 179 publications
(205 citation statements)
references
References 39 publications
8
192
0
5
Order By: Relevance
“…The validity of previous studies, which used equilibrium theories to extract mechanical information on the RBC membrane, has therefore to be critically checked. The comparison of the dissipative response for the three conditions (zero, partial and full ATP depletion) in figure 2c confirms the strong metabolic dependence of passive membrane properties noted previously 6,12,18,22,23 .…”
Section: Main Textsupporting
confidence: 69%
See 2 more Smart Citations
“…The validity of previous studies, which used equilibrium theories to extract mechanical information on the RBC membrane, has therefore to be critically checked. The comparison of the dissipative response for the three conditions (zero, partial and full ATP depletion) in figure 2c confirms the strong metabolic dependence of passive membrane properties noted previously 6,12,18,22,23 .…”
Section: Main Textsupporting
confidence: 69%
“…However, the passive mechanical properties of the RBC membrane themselves depend strongly on ATP, as illustrated by the stiffening of the RBC membrane on starvation [17][18][19]6,15 , that correlates with a sudden transition from discocyte to spiculated echinocyte shapes 20,21 . Therefore a direct and compelling explanation for the decrease of fluctuations observed in ATP-depleted cells is the stiffening of the membrane 22,23 rather than the loss of putative active (that is, non-equilibrium) fluctuations. To make a different assessment of the involvement of metabolic activity in flickering, an attractive approach was used by Tuvia et al 14 : at equilibrium, the mean-square fluctuations amplitude is a thermodynamic variable, which, by definition, cannot depend on the dynamics, and in particular on medium viscosity.…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…This phosphorylation is catalyzed by protein kinase C (PKC), which disassembles the spectrin/actin/4.1 trimer, the essential cytoskeletal complex that determines the mechanical stability of the RBC membrane (12). Indeed, PKC activation is known to lead to a decreased overall stability of the membrane skeleton (12,53,54), a structural effect that is consistent with a measurable increase of the dynamic fluctuations of the RBC membrane, as revealed by Betz et al (7). Therefore, assuming the currently accepted mechanochemical model of the 4.1 nodes (51,53), every unpinning event bears a reaction kicking force that should be stressed on the lipid membrane upon dissociation of a spectrin filament from the junctional complex (14,26).…”
Section: Cytoskeleton Pinning and Active Dynamicsmentioning
confidence: 99%
“…The FA domain of the FERM-FA proteins contains conserved motifs for PKC and PKA (Bains, 2006), suggesting that the FA domain plays a regulatory role. For instance, a previous study showed that phosphorylation of the FA domain of 4.1R by PKC interfered with its ability to form a ternary complex with spectrin and actin, which resulted in reduced membrane stability (Manno et al, 2005). The band 4.1 proteins have also been shown to interact with and regulate the membrane localization of various receptors.…”
Section: Introductionmentioning
confidence: 99%